Neuroglobin in rat brain neurons - E. V. Uzlova; S. M. Zimatkin (Сибирский научный медицинский журнал, 2021)
Neuroglobin is a metalloprotein expressed predominantly in a nervous system and involved in the functioning of cells in normal and pathological conditions. Despite numerous studies, information on its regional distribution is ambiguous. The purpose of the study is to identify patterns and features of the regional distribution of neuroglobin in neurons of all structures of the rat brain with a quantitative assessment of its content at the cellular level. Material and methods. Five outbred male rats kept under standard conditions were used in the study. Frontal serial sections were made after decapitation, fixation, dehydration and paraffin-embedding. One section of the series was stained according to the Nissl method for identification of structures according to the stereotaxic atlas, and the second section was immunohistochemically stained for neuroglobin. 100 brain structures were studied cytophotometrically, neuroglobin immunoreactivity was expressed in units of optical density ×103 (conventional units). Results and discussion. Four levels of neuroglobin content were identified – low, moderate, high and very high. Structures without neuroglobin were not found. Among the studied brain structures the amount of neuroglobin contents varies from 140–160 to 459–479 relative units. The low and moderate neuroglobin amount was revealed in supreme number of structures. Among the parts of the brain there is an increase in the content of neuroglobin in the direction telencephalon – diencephalon – midbrain – pons and medulla oblongata. The widest range of values is found in the telencephalon, pons and medulla oblongata. In the cerebellum the largest values are demonstrated by the interposed nucleus and the Purkinje cells of the pyramid. Conclusion. Neuroglobin has been found in neurons in all parts of the rat brain and spinal cord. The amount of neuroglobin depends on phylogenetic age: in the brain its content increases in the anteroposterior direction, and structures of paleocortex contain more neuroglobin than the structures of the neocortex. In the cerebellum a greater amount of neuroglobin is found in structures of the paleocerebellum.